ANALYSIS OF FINANCIAL RATIOS TO MEASURE LOCAL GOVERNMENT PERFORMANCE IN LOMBOK EAST DISTRICT - Wulandari, Erina; Ningsih, Saptia; Yulianti, Siti Maolida; Azkia, Tina Imro'atun; Damayanti, Yeni (Laboratorium Riset Ekonomi, 2022)
The local government is an institution that has an obligation to carry out development plans and services to the community, so the regional government must inform its regional accountability report to be assessed by the community whether the local government has been able to carry out its duties optimally or not. The tool used to analyze the performance of local governments in managing their regional finances is to apply financial ratio analysis to the budget and realization of the planned APBD. The research method used in this study is a descriptive analysis method through a ratio calculation approach. This research method aims to be able to provide an overview of the financial performance of the local government of East Lombok Regency from 20018-2021. The results showed that the effectiveness ratio was very effective with a total percentage of 95.71, the independence ratio showed an indicator that was less effective with a total percentage of 16.14, the ratio of financial performance activity showed an average percentage value in operating costs amounted to 109.29 and capital costs amounted to 14.41 and the expenditure growth ratio was still categorized as unfavorable because the total operating expenditure was greater than the total capital expenditure. Where operating expenditures amounted to 26.96 and total capital expenditures amounted to 3.34.